Chemoenzymatic Preparation of Functional Click‐Labeled Messenger RNA. (4th March 2020) - Croce, Stefano; Serdjukow, Sascha; Carell, Thomas; Frischmuth, Thomas
Abstract: Synthetic mRNAs are promising candidates for a new class of transformative drugs that provide genetic information for patients' cells to develop their own cure. One key advancement to develop so‐called druggable mRNAs was the preparation of chemically modified mRNAs, by replacing standard bases with modified bases, such as uridine with pseudouridine, which can ameliorate the immunogenic profile and translation efficiency of the mRNA. Thus the introduction of modified nucleobases was the foundation for the clinical use of such mRNAs. Herein we describe modular and simple methods to chemoenzymatically modify mRNA. Alkyne‐ and/or azide‐modified nucleotides are enzymatically incorporated into mRNA and subsequently conjugated to fluorescent dyes using click chemistry. This allows visualization of the labeled mRNA inside cells. mRNA coding for the enhanced green fluorescent protein (eGFP) was chosen as a model system and the successful expression of eGFP demonstrated that our modified mRNA is accepted by the translation machinery. Abstract : Diversity matters ! We have developed a chemoenzymatic approach to generate chemical diversity for mRNA. By incorporating azide‐ and/or alkyne‐modified nucleotides during enzymatic synthesis, subsequent click labeling enables one to choose and introduce chemical modifications, which is usually not possible with other methods.